Surgical management of anastomotic leakage related to ovarian cancer surgery: a narrative review - Restaino, Stefano; Schierano, Sofia; Arcieri, Martina; Costantini, Barbara; Poli, Alice; Pregnolato, Sara; Terrosu, Giovanni; Calandra, Sergio; Petrillo, Marco; Pellecchia, Giulia; Lucidi, Alessandro; Klarić, Marko; et al. (Frontiers in Surgery, 2024)
This narrative review describes the state of the art in the management of anastomotic leakage in ovarian cancer. Multiple surgical procedures, including bowel resection, are often required to achieve “optimal” cytoreduction in locally advanced ovarian cancer. Intestinal anastomosis is currently the most common way to restore bowel continuity. However, in some patients, a temporary protective stoma is indicated to prevent anastomotic leakage. This is an important issue to improve surgical outcomes and until recently there has been a lack of objective data to clarify the risk factors for anastomotic leakage. This review describes the risk factors for AL associated with surgery and compares the results of recent studies. We also review the current indications for placement of a protective ileostomy and treatment options for conservative management of AL. We present two examples of practical clinical AL risk calculators, in addition to the most assessed AL risk factor. To date, the decision-making processes that lead surgeons to perform a protective ileostomy are quite heterogeneous and based on the personal experience of the surgeon, mainly depending on individual training. Three different management options after colorectal anastomosis in OC are described: conservative management, diversion ileostomy and ghost ileostomy.